PENGARUH MODEL TALKING STICK TERHADAP HASIL BELAJAR PKn PADA SISWA KELAS V SEMESTER II SD DI GUGUS I KECAMATAN GEROKGAK - Utama, IGMP (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2018)
This study aims to find out the significant differences in learning outcomes of Civics among students who were taught by the Talking Stick model and students who were taught by conventional learning in grade V students of second semester of elementary school in Gugus I of Gerokgak Subdistrict. This research is a quasi-experimental research with post test only control group design design. The population of this study is the entire class V SD in the first group of Gerokgak District with a total of 126 students. The sample was taken by random sampling technique so that it was obtained by grade V SD Negeri 3 Tukadsumaga as experiment group and class V SD Negeri 1 Tukadsumaga as control group. The instrument of data collection used in this research is objective test of Civic learning result. Data were analyzed using descriptive statistics and Independent sample t-test. The results showed that there were significant differences in the learning outcomes of Civics between students studying with the Talking Stick model and students who were taught by conventional learning. The magnitude of t_hcount is 3,048, while t_tabel at 5% significance level and db = 42 is 2.021. This means t_count> t_table. In addition, the average score of Civics learning outcomes of students who studied with the Talking Stick model (23.08) was higher than that of students taught by conventional learning (19,26). Thus, Talking Stick model model influences the learning outcomes of Civics in Grade V students of Grade II in Gugus I, Gerokgak Sub District, Lesson Year 2017/2018. Suggestions for further research are expected to result in this research can be reused in other lessons.Keywords: talking stick, Civic learning outcomes